СARBAPENEMASE-PRODUCING GRAM-NEGATIVE BACTERIA IN A SPECIALIZED HOSPITAL OF ST. PETERSBURG - A. G. Polischouk (Sankt-Peterburg : NIIÈM imeni Pastera, 2017)
Species composition, susceptibility to antimicrobial agents, incidence and type of carbapenemase of carbapenemase-producing gram-negative bacteria, isolated in the Russian Research Centre of Radiology and Surgical Technologies from February 2014 to April 2016 were described. Screening of carbapenem-resistant bacteria was conducted by plating biomaterial on the chromogenic medium (“CHROMagar KPC”, DRG, France), species identification by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) on the analyzer VITEK MS (bioMé- rieux, France). The sensitivity of gram-negative bacteria to antimicrobial drugs was determined on the analyzer VITEK-2 (bioMérieux), and the obtained results were interpreted in accordance with EUCAST criteria v.6.0, 2016. Genes encoding carbapenemase of KPC, OXA-48/162, VIM, IMP, NDM, OXA-51, OXA40/24, OXA-23 and OXA-58 groups were detected by multiplex real-time PCR (AmpliSens, Russia). 813 clinically relevant bacteria (602 patients) were obtained, including 405 gram-negative, among which 5.2% (21 strain from 16 patients) non-susceptible to meropenem and/or imipenem: Klebsiella pneumoniae (n = 5), Enterobacter cloacae (n = 2), Serratia marcescens (n = 1), Pseudomonas aeruginosa (n = 3), Acinetobacter baumannii (n = 10). Clinical material from 4 patients was infected by up to 3 carbapenem-non-susceptible strains of different species of gram-negative bacteria at the same time. The genes encoding acquired carbapenemases were detected in 84% of the nonsusceptible to carbapenems isolates: in A. baumannii — OXA40/24 (n = 8); in K. pneumoniae — OXA-48 (n = 1), KPC (n = 1) and NDM (n = 2); in P. aeruginosa — VIM (n = 1) and KPC (n = 1); in E. cloacae — KPC (n = 1). OXA-48 carbapenemase was also detected in one carbapenem-sensitive strain of K. pneumonia. All carbapenemase-producing strains had a phenotype of multidrug resistance. The results of the study showed that over the analyzed period, the prevalence of the carbapenem-nonsusceptible strains of gram-negative bacteria were relatively low, but all these strains were multidrug resistant and most of them possessed acquired carbapenemase genes. The species carbapenemnonsusceptible gram-negative bacteria and the types of the detected acquired carbapenemase were typical for Russia. For K. pneumoniae and P. aeruginosa no predominance of any one type of carbapenemase was revealed, while in all strains of A. baumannii the gene of OXA40/24 carbapenemase was found.